Different Dreams, Same Bed : Collecting, Using, and Interpreting Employment Statistics in Sub-Saharan Africa--The Case of Uganda - Fox, Louise; Pimhidzai, Obert (World Bank, Washington, DC, 2013)
Employment and earnings statistics are the key link between the size and structure of economic growth and the welfare of households, which is the ultimate goal of development policy, so it is important to monitor employment outcomes consistently. A cursory review of employment data for low-income Sub-Saharan African countries shows both large gaps and improbable variation within countries over time and among countries, suggesting that low quality data are routinely reported by national statistics offices. Unfortunately, policies are formed and projects developed and implemented on the basis of these statistics. Therefore, errors of measurement could be having profound implications on the strategic priorities and policies of a country. This paper explains the improbable results observed by using data from Uganda, where the labor module contains variation both within and across surveys, to show the sensitivity of employment outcomes to survey methodology. It finds that estimates of employment outcomes are unreliable if the questionnaire did not use screening questions, as labor force participation will be underestimated. Likewise, surveys that use a seven-day recall period underestimate or potentially misrepresent employment outcomes, owing to seasonality and multiple jobs. Common multivariate analysis applied on household survey data will be affected, as the errors in measurement in the dependent and independent variables will be correlated. Corrections to reduce measurement bias in existing data are tested with the survey data; none are found to be completely satisfactory. The paper concludes that there is a knowledge gap about employment outcomes in Sub-Saharan Africa that will continue unless collection techniques improve.